2017
DOI: 10.1021/acsnano.6b04721
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-epitaxial Metal-Halide Perovskite Ligand Shells on PbS Nanocrystals

Abstract: Epitaxial growth techniques enable nearly defect free heterostructures with coherent interfaces, which are of utmost importance for high performance electronic devices. While high-vacuum technology-based growth techniques are state-of-the art, here we pursue a purely solution processed approach to obtain nanocrystals with eptaxially coherent and quasi-lattice matched inorganic ligand shells. Octahedral metal-halide clusters, respectively 0-dimensional perovskites, were employed as ligands to match the coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 73 publications
0
109
1
1
Order By: Relevance
“…[23] Similarly, by reducing the perovskite matrix to a thickness of monolayer on the PbS CQD, an approximate model of BiI 6 3− epitaxial ligand shell on PbS CQD was demonstrated by Sytnyk et al [26] Based on the support from these reports, we constructed a coherent interfacial model between PbS and CsPbI 3 -P as shown in Figure 2f that may explain the growth of CsPbI 3 -P on the PbS CQD. [23] Similarly, by reducing the perovskite matrix to a thickness of monolayer on the PbS CQD, an approximate model of BiI 6 3− epitaxial ligand shell on PbS CQD was demonstrated by Sytnyk et al [26] Based on the support from these reports, we constructed a coherent interfacial model between PbS and CsPbI 3 -P as shown in Figure 2f that may explain the growth of CsPbI 3 -P on the PbS CQD.…”
Section: Pbs-cspbi 3 -P Cqd Solidmentioning
confidence: 65%
See 2 more Smart Citations
“…[23] Similarly, by reducing the perovskite matrix to a thickness of monolayer on the PbS CQD, an approximate model of BiI 6 3− epitaxial ligand shell on PbS CQD was demonstrated by Sytnyk et al [26] Based on the support from these reports, we constructed a coherent interfacial model between PbS and CsPbI 3 -P as shown in Figure 2f that may explain the growth of CsPbI 3 -P on the PbS CQD. [23] Similarly, by reducing the perovskite matrix to a thickness of monolayer on the PbS CQD, an approximate model of BiI 6 3− epitaxial ligand shell on PbS CQD was demonstrated by Sytnyk et al [26] Based on the support from these reports, we constructed a coherent interfacial model between PbS and CsPbI 3 -P as shown in Figure 2f that may explain the growth of CsPbI 3 -P on the PbS CQD.…”
Section: Pbs-cspbi 3 -P Cqd Solidmentioning
confidence: 65%
“…[23] Similarly, by reducing the perovskite matrix to a thickness of monolayer on the PbS CQD, an approximate model of BiI 6 3− epitaxial ligand shell on PbS CQD was demonstrated by Sytnyk et al [26] Based on the support from these reports, we constructed a coherent interfacial model between PbS and CsPbI 3 -P as shown in Figure 2f that may explain the growth of CsPbI 3 -P on the PbS CQD. As demonstrated by Sytnyk et al, [26] to form the perovskite ligand shell on PbS CQD surface, the perovskite octahedral ligand have to coalesce on the CQD surface so that the adhering neighboring octahedral share edge and corner ions ( Figure 2f). As demonstrated by Sytnyk et al, [26] to form the perovskite ligand shell on PbS CQD surface, the perovskite octahedral ligand have to coalesce on the CQD surface so that the adhering neighboring octahedral share edge and corner ions ( Figure 2f).…”
Section: Pbs-cspbi 3 -P Cqd Solidmentioning
confidence: 65%
See 1 more Smart Citation
“…Nearly defect‐free heterostructures with coherent interfaces are of the utmost importance for high‐performance electronic devices. Different octahedral metal‐halide clusters ((CH 3 NH 3 + ) (6− x ) [M ( x +) Hal 6 ] (6− x )− , M x + = Pb(II), Bi(III), Mn(II), In(III), Hal = Cl, I) and 0D perovskites were also employed as ligands to match the lattice of PbS QDs via a solution‐processing approach by Sytnyk et al The photoconducting devices with MA 3 BiI 6 ligands showed a high detectivity of 2 × 10 11 cm Hz 1/2 W −1 with an over 110 kHz bandwidth due to the small relative lattice mismatch of ≈−1%. The results showed that quasiepitaxial ligand shells were formed on NCs by the selection of ligands with appropriate geometry and optimized bond lengths, which are beneficial for applications in optoelectronics.…”
Section: Hybrid Structure Of Halide‐perovskite‐based Photodetectorsmentioning
confidence: 99%
“…In addition to the highly successful application of perovskite materials in solar cells with photo‐to‐electric conversion efficiency increasing from 3.8% to 22.1% within past few years, advancements in halide perovskite photodetectors (HPPDs) incorporated with different dimensional materials have also been achieved, such as 0D (quantum dots (QDs): PbS, ZnS, PbSe, etc. ), 1D (nanowires or nanowire arrays: ZnO, TiO 2 , carbon nanotubes (CNTs), etc.…”
Section: Introductionmentioning
confidence: 99%